Municipal Services Problems in Mosul Vilayet During the Ottoman Era 1869–1918 AD (Journal of the College of Basic Education, 2026)
The municipality was one of the most important administrative and service institutions formed during the Ottoman era, operating in various provinces, including the Mosul province, which held a prominent position among the Ottoman provinces of that era. This institution's organizational structure consisted of several administrative and service units, each according to its tasks and responsibilities in providing public services to the province. Despite providing all services to the people of the province in various areas required by the province, it faced numerous problems in performing its duties. Financial problems were among the most important of these problems, as well as how to obtain funding and a budget to cover its expenses and implement its projects, especially since its budget came from the Sublime Porte, which was often delayed for long periods and sometimes almost not spent. This forced it to impose multiple taxes to cover these expenses, which burdened many professions and caused significant problems in the province, in addition to other multiple problems. In light of this, our study aims to shed light on the most important problems of municipal services in the Mosul province during the Ottoman era, specifically during the period 1869-1918 AD.